Abolition of Biofilm Formation in Urinary Tract Escherichia coli and Klebsiella Isolates by Metal Interference through Competition for Fur - Hancock, Viktoria (American Society for Microbiology (ASM), 2010)
Bacterial biofilms are associated with a large number of persistent and chronic infections. Biofilm-dwelling bacteria are particularly resistant to antibiotics and immune defenses, which makes it hard if not impossible to eradicate biofilm-associated infections. In the urinary tract, free iron is strictly limited but is critical for bacterial growth. Biofilm-associated Escherichia coli cells are particularly desperate for iron. An attractive way of inhibiting biofilm formation is to fool the bacterial regulatory system for iron uptake. Here, we demonstrate that biofilm formation can be impaired by the addition of divalent metal ions, such as Zn(II) and Co(II), which inhibit iron uptake by virtue of their higher-than-iron affinity for the master controller protein of iron uptake, Fur. Reduced biofilm formation of urinary tract-infectious E. coli strains in the presence of Zn(II) was observed in microtiter plates and flow chambers as well as on urinary catheters. These results further support that iron uptake is indeed crucial for biofilm formation, and thereby, targeting these uptake systems might be an effective way to eradicate biofilms caused by infectious strains.